The Roman Agora at Athens Revisited: Pottery Evidence for the Monument’s Construction and the Function of the Area in the post-Sullan Era - Grigoropoulos, Dimitris; Panagou, Tania; Sourlas, Dimitris (Rei Cretariae Romanae Fautorum Acta, 2024)
The so-called Market of Caesar and Augustus is one of the most prominent monuments of Roman Athens, whose chronology and original date of construction still pose problems. Deep excavation carried out by the Ephorate of Antiquities of the City of Athens below the west stoa yielded deposits relating to the foundation of the building complex, including a rich assortment of ceramics of all functional categories from various eastern and western sources. In addition to providing pottery evidence for dating the market’s foundation, the finds contribute new data regarding the function of the area prior to the construction of the Roman Agora and shed light onto the still little-known pottery supply of the city in the post-Sullan and Early Augustan period.